ANALISIS PENGHEMATAN BIAYA OBAT MELALUI SUBSTITUSI GENERIK PADA KARYAWAN PT KORINDO ARIABIMA SARI DI KOTAWARINGIN BARAT - , MIA ANDRIYANI, Prof. Dr. Dra. Sri Suryawati, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The problem on health financing always becomes an issue that may alienate the public from health care centers. Drug costs take a significant proportion and may be an intervention tool to improve health status. Efforts to make drug-cost savings by private companies have often been made. However, there are not many data that can be disclosed. Drug-cost savings made to control health funding by the private companies can be done by the selection of drugs through generic substitution. Methods: This is a case study using descriptive analysis. The quantitative data were collected from the prescribing of the companyâs outpatient employees within January 2013 - March 2013. The qualitative data were collected by conducted indepth interviews to reveal the opinions of the key stakeholders to the private companies, the doctor prescribers, and the pharmacists managing pharmacies about the generic substitution which had been done. Research findings: The findings of this research indicated the presence of drugcost savings before and after the generic substitution was implemented by 19% towards 1179 prescription sheets with the number of R/ as many as 3476. The number of R / written using the generic name was 23%, the number of R / substituted was 21%, and the number of R / not substituted was 56%. The opportunity for further savings can be improved through the drugs which have not been substituted and through the drug substitution following the therapy groups of anti-infective drugs (32%) and cardiovascular drugs (13%). This substitution policy is considered important by the company because it can reduce drug financing spent on the implementation of the employee health system. Conclusions: Drug-cost savings made by PT Korindo Ariabima Sari is considered important since the savings could reduce drug financing by Rp16.332.300, - or 19%, with the average number of R/ prescription sheet was 3 and the percentage of the drugs handed over using the generic name was 23% and the percentage of the patients receiving vitamin and supplement prescriptions was 7% without decreasing the quality of the services from the doctors.